What drives corporate social performance? The role of nation-level institutions - Ioannou, Ioannis; Serafeim, George (Journal of International Business Studies, 2012)
Based on Whitley's “national business systems” (NBS) institutional framework, we theorize about and empirically investigate the impact of nation-level institutions on firms’ corporate social performance (CSP). Using a sample of firms from 42 countries spanning seven years, we construct an annual composite CSP index for each firm, based on social and environmental metrics. We find that the political system, followed by the labor and education system, and the cultural system are the most important NBS categories of institutions that impact CSP. Interestingly, the financial system appears to have a relatively less significant impact. We discuss implications for research, practice and policymaking.